The Transformative Power of Literature: English Lecturers’ Views on Fostering Ecoliteracy in Higher Education - Neni Nurkhamidah (Universitas Veteran Bangun Nusantara, 2025)
This study explores English lecturers’ perceptions, experiences, and challenges in implementing literature infused with ecoliteracy in English language teaching at the higher education level. As environmental issues become increasingly critical, fostering ecoliteracy has emerged as a key educational objective. Using a qualitative research design, the study employed semi-structured interviews with three English lecturers at MNC University, an institution committed to sustainability and interdisciplinary education. Thematic analysis revealed that lecturers view literary texts as effective tools for promoting environmental awareness, critical thinking, and student engagement. Genres such as poetry, fiction, and drama were identified as particularly impactful for embedding ecological themes. The lecturers implemented a range of teaching methods, including project-based learning, group discussion, and performance, to enhance ecoliteracy in their classrooms. However, challenges such as limited curriculum flexibility, student disengagement, and inadequate institutional resources were also reported. Despite these barriers, the lecturers agreed that implementing ecoliteracy through literature enriches language instruction and promotes socially and environmentally conscious learning. This research contributes to the discourse on sustainable education by highlighting the transformative role of ecoliterary practices in English language teaching and offering practical insights for curriculum development and teacher training.